2008 American Control Conference 2008
DOI: 10.1109/acc.2008.4586616
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive output feedback control for complex-valued reaction-advection-diffusion systems

Abstract: We study a problem of output feedback stabilization of complex-valued reaction-advection-diffusion systems with parametric uncertainties (these systems can also be viewed as coupled parabolic PDEs). Both sensing and actuation are performed at the boundary of the PDE domain and the unknown parameters are allowed to be spatially varying. First, we transform the original system into the form where unknown functional parameters multiply the output, which can be viewed as a PDE analog of observer canonical form. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…where 􏽢 w 0 is the initial value of the observer (8), w 0 is the initial value of the original system (1), and M, ω and M 1 , ω 1 are constants in (13) and (23), respectively.…”
Section: Design Of Observer and Predictormentioning
confidence: 99%
See 1 more Smart Citation
“…where 􏽢 w 0 is the initial value of the observer (8), w 0 is the initial value of the original system (1), and M, ω and M 1 , ω 1 are constants in (13) and (23), respectively.…”
Section: Design Of Observer and Predictormentioning
confidence: 99%
“…In the past decades, much effort has been made for the problems of unstable or antistable infinite-dimensional systems which can be applied to practical engineering (see [1][2][3][4][5][6][7][8][9][10][11][12][13]). For example, reference [14] relates the loss of the heat to the surrounding medium and the destabilizing heat generation inside the rod.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the continuous development of neural network theory, it has been found that real-valued neural networks have some limitations when solving many practical application problems, for example XOR [20], reaction-convection-diffusion systems [21,22], etc. Thus, as a extension of real-valued neural network, the complex-valued neural network has been adopted and investigated in depth since they have a more complex structure and richer properties, which can solve the above problems more easily and effectively.…”
Section: Introductionmentioning
confidence: 99%